Activity Of 70% Ethanol Extract From Moringa Olefera Leaves (Moringa oleifera Lam.) On Wound Healing In Hyperglycemia Rats - Sarah Zaidan; Novi Yantih; Diah Pratami; Aiy Pengasih (Indonesian Journal Publisher, 2026)
This study aimed to evaluate the wound healing profile in hyperglycemic rats treated with 70% ethanolic extract of Moringa oleifera Lam. leaves compared with povidone iodine, to determine the most effective extract concentration, and to assess the quality of the leaf extract. The extract was prepared using 70% ethanol maceration and evaluated for yield, moisture content, pH, total flavonoid content, and quercetin levels. Twenty-five rats were divided into five groups: negative control, positive control (povidone iodine), and extract concentrations of 5%, 10%, and 15%. A 2-cm dorsal incised wound was created on each rat, followed by once-daily topical application for 14 days. Macroscopic observations included wound closure, scab formation, and hair growth. Quality evaluation showed a yield of 23.8% (≥ 9.2%), moisture content of 4.05% (< 10%), pH of 5.70 (4.5–6.0), total flavonoid content of 2.58 mg QE/g, and quercetin content of 0.69%. Wound-healing analysis demonstrated significant differences between groups, with a p-value of 0.001 (p < 0.05). The mean percentage of wound-area reduction was 95% for the 5% extract, 94.71% for the 10% extract, 95.87% for the 15% extract, and 90.37% for the positive control group. The 15% extract was the most effective in accelerating scab formation and hair growth. In conclusion, especially at the 15% concentration, the ethanol extract of Moringa oleifera leaves demonstrated good extract quality and successfully accelerated wound healing in hyperglycemic rats.